THE EFFECT OF HUMAN RESOURCES AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT THE HUMAN RESOURCES AND HUMAN RESOURCES DEVELOPMENT AGENCY (BKPSDM) OF MESUJI REGENCY - Aspar, TB Reza; Parela, Epi; Zainuddin, Bustami (University of Sang Bumi Ruwa Jurai, 2025)
The main objective of human resource development is to improve employee performance. Through human resource development activities, it is hoped that there will be an increase in the knowledge, skills, and work attitude of employees towards the tasks for which they are responsible. Human resource development does not only focus on technical abilities, but also on the formation of a positive mental attitude that encourages employees to continuously improve their performance quality. Basically, performance is a perspective and mental attitude that always strives to be better over time—today must be better than yesterday, and tomorrow must be better than today. This study uses a quantitative descriptive method, which is a method that analyzes numerical data to explain the relationship between variables in a population. In this study, simple and multiple regression analysis techniques were used with a total of 38 employee respondents. The analysis results show that there is a significant influence between human resource development and employee performance at the Mesuji Regency Civil Service and Human Resource Development Agency, with a coefficient of determination (R-square) of 77.9%. In addition, organizational culture also influences employee performance with an influence level of 49.5%. Simultaneously, human resource development and organizational culture have a strong influence on employee performance, with an influence level of 88%. These results show that improving the quality of human resources and strengthening organizational culture together can contribute significantly to improving employee performance